Satellite Image Data as Environmental Crime Evidence in the Field of Illegal Logging - Mahfud Mahfud; Lena Farsia; Nellyana Roesa; Safrina Safrina (Fiat Justisia: Jurnal Ilmu Hukum, 2021)
Indonesia's forest degradation which is triggered by decades of uncontrolled deforestation has caused massive tropical forest depletion. The same situation also happened to Aceh's forest whose forest areas have been shrinking from year to year.  Indication of the increase in illegal logging is both in Indonesia and especially in Aceh as if showing an indication and an academic conclusion that there is a crucial problem. Therefore, there is a need for a mechanism to create an effective legal role to at least reduce illegal logging that is increasingly prevalent in Indonesia's forests. One of the mechanisms is by using a remote sensing technology approach to monitor the occurrence of illegal logging or other criminal acts in the forest which are considered to be the cause of the loss of Aceh's forest in particular and Indonesia in general. This study aims to find out the use of remote sensing satellite technology to monitor illegal logging in Aceh and to identify the use of satellite imagery by law enforcement officials in Aceh to punish illegal logging offenders. The results showed that law enforcement officers used satellite imagery data on conditions before and after environmental damage in handling illegal logging.   However,   the data that emerged from   LAPAN   is rarely used by law enforcement officials to monitor the condition of national forests, especially those in their work areas. Lack of use of satellite data by law enforcement officials in the initial tracking to eradicate illegal logging due to their lack of initiative to prevent illegal logging, the physical condition of  Leuser protected forest areas which are also close to residential areas,   and external issues of areas that make wood from Aceh's forests are traded outside the region and even abroad, as well as the lack of qualifications of law enforcement officials who know the environmental issues.